Theoretical Study of 1,3-Dipolar Cycloaddition Reaction of Aryl Azide and its Derivatives with Cinnamic Acid one in Gas State and with Different Solvents (Latakia University Journal -Basic Sciences Series, 2018)
The 1,3-dipolar cycloaddition of the aryl azide and some its of derivatives with cinnamic acid was studied theoretically using different methods of  Density Functional Theory (DFT): B3LYP, B3PW91, MPW1PBE, MPW1PW91 and M062X with the basic set 6-31g(d). Most of the used levels of theories provide closed results qualitatively, and the results of the level of theory  M062X / 6-31g (d) show that these reactions in the gas state carried out spontaneously to form several stable energy  products; the products P1 and P2 are most stable, but all the reactions are very slow and one of the products P1 is more spontaneous than P2 , but the formation reaction of  P2 is faster.On the other hand, when these reactions were studied with different solvents, it is found that solvents to have no actual effects on the rates of these reactions.The results of the level of theory M062X/6-31g(d) indicate that the Gibbs free energy of the reactions for the substitutes of Aryl azide increases in negative values in order of  2,6-Cl, 4-NO2, 4-OCH3, 3-OCH3, 3-Cl, 2 -Cl, H- for P1, and of 2,6-Cl, 4-OCH3, 3-OCH3, 2-Cl, 4-NO2, -H, 3-Cl; i.e. the substitutes do not have a significant effect on the spontaneity of reactions compared to the substitute –H. It was observed that TS-P2 transition state energy for all substitutes was lower than TS-P1 transition state energy.